The Degree of Exercise of secondary school principals in the Kasbah Al-Mafraq district of administrative delegation in light of the Corona pandemic - Al-Amoush, Kholoud Mohammed (Journal of Educational and Psychological Sciences, 2021)
This study aimed at revealing the programs of secondary school principals’ practice in the general beginning of delegation and administrative delegation in light of the general rule from their point of view. The researcher used the descriptive approach، and the beginning was represented by a questionnaire consisting of (30) ... distributed to a stratified sample of (74) principals and interested persons in the whole community in secondary schools in Kasbah Al-Mafraq District، and the most prominent results of the study in the stage of practicing secondary schools in Kasbah Al-Mafraq district for administrative delegation in light of the Corona pandemic، from their point of view، obtained an overall average (2.39 out of 3) with a high degree (high ) and at a level; The domain of delegation in the administrative domain got the highest average (2.48) then the educational domain with an average of (2.37)، both with a degree of delegation (high) in the domain، terms and responsibilities with an average of (2.33) (medium) and there were no statistically significant differences at the level of ( 0.05≥α) in 2014 was re-developed article.
Keywords: degree of practice; secondary school principals; Mafraq district; administrative delegation; Corona regulation